மரபுவழி அடையாளமும் வாழும் நாட்டின் அடையாளமும் எழுத்தாளர் கே. எஸ். மணியம் படைப்புகளில் அடையாளத் தேடல்கள் (Heritage identity and the identity of the living country: Searching the Truths in the Writings of K. S. Maniam) - Maruthaveeran, Vijaletchumi (Journal of Indian Studies (இந்திய ஆய்விதழ்), 2020)
Almost all literary works of K.S.Maniam, regardless to genre, i.e., short stories, Novels, and Dramas, have touched the live-circle of migrant community in Malaysia. His works have discussed the milieus facing the community and the solutions for better livelihood in the foreign land for the migrants. K.S.Maniam’s literary works, in particular, projects ways in which the migrant community could receive in and accept the assimilation of the local cultural essences to form a true Malaysian-based cultural infusions. For his significant contributions, the author has been honoured with the honorary award of Rajah Rao, so far. Beyond this, his monumental work, ‘The Return’ novel and a few short-stories have been used as literary texts in the secondary schools, as well. Unfortunately, his works have received not much appreciation among the Indian community. This article is aimed at studying and highlighting the contributions of K.S.Maniam in promoting the sense of humanity and identity in the alienated setting among the migrant community. ஆய்வுச் சுருக்கம் எழுத்தாளர் கே.எஸ். மணியத்தின் ஆங்கில மொழி சிறுகதைகள், நாவல்கள், நாடகங்கள் அனைத்து வகை இலக்கியப் பிரதிகளும் மலாயா/மலேசியாவின் புலம்பெயர் சமூகம் இதுவரை கடந்துவந்திருக்கும் பாதையையும் இனி செல்ல வேண்டிய இலக்கையும் அதற்கான வழிகளையும் மீளாய்வு செய்பவை. ஒவ்வொரு சமூக உறுப்பினரும் தனது மரபுவழி அடையாளங்களையும் வாழும் நாட்டின் அடையாளங்களையும் ஒருங்கே அணைத்துக் கொள்வதன்வழி பன்முகத் தன்மைகொண்ட ஒன்றைச் சமூகமாக உருவெடுக்க முடியும் எனும் பெரும் எதிர்பார்ப்பை கே.எஸ். மணியத்தின் படைப்புகள் முன்வைக்கின்றன. இதுவரையில் இவரது படைப்புக்கு கிடைத்த மிக உயரிய அங்கிகாரம் ராஜா ராவ் விருது ஆகும். இதைத் தவிர அவருடைய ‘The Return’ நாவலும் இதர சில சிறுகதைகளும் இடைநிலைப் பள்ளிகளில் ஆங்கில இலக்கியப் பாட நூல்களாகப் பயன்படுத்தப்பட்டதும் குறிப்பிடத்தக்க விடயமாகும். மலேசிய ஆங்கில இலக்கியச் சூழலில் முன்னோடியாகத் திகழும் கே.எஸ்.மணியத்தின் படைப்புகளில் வெளிப்படும் தனிமனித, சமூக அடையாளத் தேடல்கள்; அதை நோக்கிய பயணங்களின் சுவடுகளை அடையாளம் கண்டு விளக்க இக்கட்டுரை முனைந்துள்ளது.